Comparison of Zebrafish tmem88a mutant and morpholino knockdown phenotypes. - Alexander M J Eve; Elsie S Place; James C Smith (PLoS ONE)
Tmem88a is a transmembrane protein that is thought to be a negative regulator of the Wnt signalling pathway. Several groups have used antisense morpholino oligonucleotides in an effort to characterise the role of tmem88a in zebrafish cardiovascular development, but they have not obtained consistent results. Here, we generate an 8 bp deletion in the coding region of the tmem88a locus using TALENs, and we have gone on to establish a viable homozygous tmem88aΔ8 mutant line. Although tmem88aΔ8 mutants have reduced expression of some key haematopoietic genes, differentiation of erythrocytes and neutrophils is unaffected, contradicting our previous study using antisense morpholino oligonucleotides. We find that expression of the tmem88a paralogue tmem88b is not significantly changed in tmem88aΔ8 mutants and injection of the tmem88a splice-blocking morpholino oligonucleotide into tmem88aΔ8 mutants recapitulates the reduction of erythrocytes observed in morphants using o-Dianisidine. This suggests that there is a partial, but inessential, requirement for tmem88a during haematopoiesis and that morpholino injection exacerbates this phenotype in tmem88a morpholino knockdown embryos.